Sosialisai Pemahaman Tentang Apa Itu Olahraga Rekreasi dan Apa Itu Olahraga Prestasi di Desa Padang Batu - Ajis Sumantri; Nikentry Agustinah (Jurnal Dehasen Untuk Negeri, 2024)
ecreational sports are physical pursuits that are done for enjoyment, relaxation, and amusement rather than under pressure to meet predetermined goals or standards. Developing mental and physical well-being is the primary goal. The purpose of engaging in different activities, like hiking, cycling, or swimming, is to pass the time and interact with others. Recreational sports foster a calm and encouraging atmosphere that helps people socialize, form friendships, and enhance their general wellbeing. Meanwhile, sports performance on the other hand, refers to physical activity done primarily for the purpose of accomplishing certain goals, such as winning a game, setting a personal record, or receiving an honor. To reach a level of excellence, competitors compete at a high level and concentrate on rigorous training and skill development. Achievements in sports are frequently linked to competitiveness, prestige, and recognition. Performance sports socialization encompasses experience sharing, a sense of community, and teamwork, fostering an atmosphere that encourages athletes to reach their goals.